If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + 2x) * 2 = 2 + 0x Reorder the terms for easier multiplication: 2(3 + 2x) = 2 + 0x (3 * 2 + 2x * 2) = 2 + 0x (6 + 4x) = 2 + 0x Anything times zero is zero. 6 + 4x = 2 + 0x Combine like terms: 2 + 0 = 2 6 + 4x = 2 Solving 6 + 4x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 2 + -6 4x = 2 + -6 Combine like terms: 2 + -6 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| X^4+13x^3-48x^2=0 | | 0=2*sin(2x) | | 8v+w+7-8w+2w= | | m+3.5=4.2 | | 2(3h-7)=76 | | 3x+(-3x)=5 | | 2+3x+4-1= | | 0.16y+0.08(y+9000)=2400 | | 6(t-3)+4t=5(2t+5)-13 | | .11x-400-.03x=840 | | 4x+6+3x+4=(-40)+4 | | 3z-836=-77 | | Y+8=2y-4 | | -3x+10=94+4x | | 5y^2-7y=-2 | | 27=3(2x-7) | | -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 |